2018
DOI: 10.1590/2317-1782/20182017225
|View full text |Cite
|
Sign up to set email alerts
|

Características acústicas de vozes saudáveis de adultos: da idade jovem à meia-idade

Abstract: RESUMO Objetivo Caracterizar as vozes de indivíduos adultos sem queixas vocais e verificar o efeito de gênero e idade a partir de um conjunto de medidas acústicas. Método Foram analisadas 176 gravações de vozes pertencentes a adultos com idades entre 19 e 59 anos, divididas em quatro grupos etários, por década, armazenadas em uma base de dados. Todas as vozes analisadas foram classificadas com ausência de desvio na qualidade vocal. Realizou-se análise acústica dos parâmetros: Frequência Fundamental (vogal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The studies were grouped together according to the acoustic measurements explored: F 0 , jitter, shimmer, and noise measurements. This organization was proposed because they are the most commonly investigated ones for the description of vocal behavior in normal 5,12,13,14 and pathological 13,15 conditions, besides being possible to be analyzed through distinct acoustic analysis software 7 . Hence, such organization was chosen in order to favor the verification of acoustic changes in voice production occurred throughout life.…”
Section: Fundamental Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were grouped together according to the acoustic measurements explored: F 0 , jitter, shimmer, and noise measurements. This organization was proposed because they are the most commonly investigated ones for the description of vocal behavior in normal 5,12,13,14 and pathological 13,15 conditions, besides being possible to be analyzed through distinct acoustic analysis software 7 . Hence, such organization was chosen in order to favor the verification of acoustic changes in voice production occurred throughout life.…”
Section: Fundamental Frequencymentioning
confidence: 99%
“…The F 0 is found to be lower in the premenstrual period in relation to the menstrual and postmenstrual periods, because of the increase in mass in the vocal folds resulting from hormonal changes 22 . Hence, during adulthood, the F 0 values are expected to be stable in young adult men and women, though in women such changes may happen prior to the menopause period 14,21 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the human body, the larynx also undergoes natural changes called presbylarynx (1) . Aging can lead to several impacts on the body, such as soft tissue atrophy, cartilage ossification and cellular alterations and, as a consequence, it results in changes in the voice that can be inferred by the acoustic analysis of the voice signal (2)(3)(4)(5) . As an inherent part of the aging process, the structural changes caused by presbyphonia can reflect on the vocal quality of the elderly (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional acoustic measures, such as Fundamental Frequency (f o ), jitter, shimmer and Noise-to-Harmonic Ratio (NHR), can differentiate genders and vocal deviation in the elderly (2) . In this context, previous studies have investigated vocal changes throughout life through acoustic measurements (2)(3)(4)(5)(6) . Regarding disturbance measures, a previous study showed higher values in the elderly, with this value being higher for men compared to women (2) .…”
Section: Introductionmentioning
confidence: 99%